2021
DOI: 10.1007/s41742-021-00351-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of Slaughterhouse Sludge in the Bioremediation of an Oxyfluorfen-Polluted Soil

Abstract: The use of organic matter is a highly accepted environmental practice among scientists for the bioremediation of polluted soils. In this manuscript we study under laboratory conditions the bioremediation capacity of a new biostimulant obtained from slaughterhouse sludge in a soil polluted by the oxyfluorfen at a rate of 4 l ha−1 (manufacturer’s rate recommended) over a 90-day period. We determined its effects on dehydrogenase, urease, β-glucosidase and phosphatase activities, the soil microbial community struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our results indicate that application of the oxyfluorfen herbicide caused an inhibition in soil dehydrogenase enzymatic activity. These results are in line with those obtained by Franco-Andreu et al (2016), Ávila-Pozo et al (2021 and Tejada et al (2022), who observed a significant toxic effect of oxyfluorfen on this intracellular enzymatic activity.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that application of the oxyfluorfen herbicide caused an inhibition in soil dehydrogenase enzymatic activity. These results are in line with those obtained by Franco-Andreu et al (2016), Ávila-Pozo et al (2021 and Tejada et al (2022), who observed a significant toxic effect of oxyfluorfen on this intracellular enzymatic activity.…”
Section: Discussionsupporting
confidence: 93%
“…Different biostimulants mainly obtained from different organic wastes by enzymatic hydrolysis processes have been used for the bioremediation of soils polluted by various herbicides in recent years [9,10,12]. The results obtained in these studies suggest that the application of these biostimulants to contaminated soils significantly decreases the herbicide concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the role of sewage sludge is the same as for other sources of organic matter applied to soils contaminated by pesticides. Thus, they play a role in stimulating pesticide-tolerant soil microorganisms, which leads to an acceleration in the degradation of this organic xenobiotic and mayo also allow the sorption of such pesticides; thus, reducing their concentration in the soil solution and, consequently, reducing their toxicity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the biostimulant, and according to Ávila-Pozo et al [14], slaughterhouse sludge was subjected to two treatments. In the first treatment, the slaughterhouse sludge was concentrated at 75 • C with a rotary evaporator until reaching a dry matter value of around 15%.…”
Section: Biostimulant Propertiesmentioning
confidence: 99%
“…There has been a marked increase in the production of slaughterhouse sludge in recent decades as a consequence of the increase in the number of such facilities [14]. These authors obtained a biostimulant from slaughterhouse sludge by way of enzymatic hydrolysis processes and used it for the bioremediation of soil contaminated with the herbicide oxyfluorfen.…”
Section: Introductionmentioning
confidence: 99%